Jump training with blood flow restriction has no effect on jump performance - Masahiro Horiuchi; Junko Endo; Takashi Sato; Koichi Okita (Termedia Publishing House, 2018)
This study investigated whether jump training with blood flow restriction (BFR) improves jump performance compared to jump training without BFR under similar exercise intensity in healthy young humans. The participants were twenty healthy males who were assigned to either jump training with BFR (n = 10) or jump training without BFR [control (CON); n = 10] groups. All subjects completed five sets of 10 repetitions with one-minute intervals of half-squat jumps (SJ) at maximal effort, four days a week for four weeks. In the BFR group, circulatory occlusion around both thigh muscles was applied at a pressure of 200 mmHg, and physical characteristics, muscle strength and jump performance were evaluated before and after training. A significant main effect of training period on lean body mass, percentage of body fat and leg circumference in both groups was observed (P < 0.05). For jump training with BFR, only knee flexion strength increased (P < 0.05), while in the CON group, both knee extension and flexion strength increased (P 0.05), whereas training without BFR (CON) improved the performance of both jumps (SJ: pre 35.7 ± 5.1 vs. post 38.9 ± 4.1 cm, P = 0.002: CMJ: pre 41.6 ± 3.6 vs. post 44.6 ± 3.8 cm, P < 0.001). These results indicate that jump training with BFR may not be an effective strategy for improving jump performance.